ARCHITECTURAL FEATURES DETACHED HOUSE MODERN AGE (Municipal economy of cities. Series: «Economy science», 2013)
The features of the era of modern architecture houses the example of historical and architectural monument - M.Kshesinskoy mansion in St. Petersburg.